Synthesis of Fluorescent Amino Acids via Palladium-Catalyzed Allylic Alkylations - Schmidt, Lisa; Doroshenko, Tamara; Barbie, Philipp; Grüter, Andreas; Jung, Gregor; Kazmaier, Uli (Synthesis, 2016)
Coumarin-derived allylic carbonates are found to be suitable electrophiles for the synthesis of fluorescent amino acids via palladium-catalyzed allylic alkylation of chelated glycine enolates. The formation of regioisomers can be suppressed by proper choice of the allyl carbonate.
Keywords: allylation; amino acids; chelates; coumarins; fluorescence labeling; palladium